Perspectives of a Telehealth and In-Person Collaborative Learning Experience on Infant Development: A Mixed-Method Study. - Fergus, Andrea; Delbridge, Ainsley; Sutton, Sydney (Physical & Occupational Therapy in Pediatrics, 2026)
Aims: This study describes the implementation and perspectives of a collaborative experiential learning experience (CELE) for understanding and examining infant development in Doctor of Physical Therapy (DPT) students. Methods: The CELE blended an in-depth telehealth analysis with a broad in-person comparative analysis of infant development. Quantitative (questionnaire) and qualitative (semi-structured interview) methodologies examined the perspectives of students, clinical instructors (CIs), and parents. Results: Over 80% of questionnaire respondents (44 students, 2 CIs, 7 parents) deemed the CELE valuable for learning and applying concepts in infant development. Similarly, over 80% of students and CIs felt the CELE promoted appreciation for natural environments and family-centered care. Thematic analyses of interviews (15 students, 4 CIs, 6 parents) highlighted the importance of the experiential and multimodal nature of the experience. Pedagogical components including structured expectations, non-intrusive and recorded feedback, peer collaboration, and reflection promoted learning. Specifically, enhanced understanding of infant development, clinical skills for pediatric and telehealth practice, appreciation for the cornerstones of pediatric rehabilitation, and the role of telehealth emerged. Conclusions: This CELE is feasible within DPT curriculum to address the need for real-life pediatric experience and can provide future clinicians with unique opportunities for growth and learning in pediatric rehabilitation and telehealth.